1991
DOI: 10.1101/gad.5.7.1191
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism regulating growth factor association with the cell surface: identification of a PDGF retention domain.

Abstract: Platelet-derived growth factor (PDGF) chimeras were used to map a domain responsible for either efficient secretion of PDGF-A or the tight cell association of PDGF-B to their carboxy-terminal domains. Introduction of stop codons within PDGF-A or PDGF-B further dissected their respective carboxy-terminal domains. Although successive deletions of the PDGF-A carboxyl terminus did not impair its secretion, incremental deletions from the carboxyl terminus of PDGF-B abrogated its membrane retention properties and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(74 citation statements)
references
References 31 publications
2
71
1
Order By: Relevance
“…This finding was initially unexpected, as the PDGF-DD(GFD) more potently transformed NIH/3T3 cells in vitro. However, considering that altered pericellular retention and/or matrix interactions are important determinants for the physiological action of many other growth factors (LaRochelle et al, 1991;Ostman et al, 1991;Carmeliet et al, 1999;Grunstein et al, 2000;Lindblom et al, 2003;Lee et al, 2005), this could be a likely mechanism for controlling the function of PDGF-DD as well. In line with this, one could speculate that the observed differences in foci morphology induced by the two PDGF-DD forms are due to different spatial distribution, especially as we have previously shown that smaller and unevenly shaped foci can be formed from NIH/3T3 cells overexpressing matrix-bound PDGF-BB (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…This finding was initially unexpected, as the PDGF-DD(GFD) more potently transformed NIH/3T3 cells in vitro. However, considering that altered pericellular retention and/or matrix interactions are important determinants for the physiological action of many other growth factors (LaRochelle et al, 1991;Ostman et al, 1991;Carmeliet et al, 1999;Grunstein et al, 2000;Lindblom et al, 2003;Lee et al, 2005), this could be a likely mechanism for controlling the function of PDGF-DD as well. In line with this, one could speculate that the observed differences in foci morphology induced by the two PDGF-DD forms are due to different spatial distribution, especially as we have previously shown that smaller and unevenly shaped foci can be formed from NIH/3T3 cells overexpressing matrix-bound PDGF-BB (Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In the blood vessel (BV) of a skin wound and atheromatous aorta, myofibroblasts (green arrow) PDGF-B and Furin were found to be expressed by different cells, suggesting a potential paracrine interaction 2002). This would result in the retention of the unprocessed and/or PC-cleaved form of PDGF-B at the cell surface, to be released in a controllable manner by a second processing event (LaRochelle et al, 1991;Andersson et al, 1994;Rolny et al, 2002). Conversely, several studies reported that deletion of the retention motif in PDGF-B leads to its increased secretion and accumulation in the cell culture media (LaRochelle et al, 1991;Andersson et al, 1994;Kaetzel et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…This would result in the retention of the unprocessed and/or PC-cleaved form of PDGF-B at the cell surface, to be released in a controllable manner by a second processing event (LaRochelle et al, 1991;Andersson et al, 1994;Rolny et al, 2002). Conversely, several studies reported that deletion of the retention motif in PDGF-B leads to its increased secretion and accumulation in the cell culture media (LaRochelle et al, 1991;Andersson et al, 1994;Kaetzel et al, 1996). In addition, the reduced secretion of PDGF-B was previously reported to limit the action range of PDGF-B in vivo, as suggested from experiments with transplanted keratinocytes expressing wild-type or retention motiftruncated PDGF-B into athymic mice (Eming et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The abilities of the mutant PDGF molecules to compete for binding of 12~I-PDGF-AA and 125I-PDGF-BB to a-and 13-receptors, respectively, were determined and compared to that of wild-type PDGF-BB. In order to achieve efficient secretion of wild-type PDGF-BB and PDGF-BB mutants, vector constructs were used coding for truncated molecules lacking the basic motif in the C-terminus of the PDGF B-chain which mediates retention intracellularly and to the extracellular matrix [15,20,21].…”
Section: J Kreysing Et Al/febs Letters 385 (1996) 181-184mentioning
confidence: 99%